Analisis Kebutuhan Dan Ketersediaan Air Irigasi Di Kalukku Dengan Metode FJ Mock - Afdal, Muhammad Wahid; Yusuf, Andi Rumpang; Cangara, Satriawati (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Water requirements in irrigation are very variable depending on land conditions and management. This research aims to determine the mainstay discharge in the watershed and water availability to meet water needs in Kalukku, Mamuju district. These needs include evaporation, plant needs, and water loss. Therefore, it is planned to determine the amount of reliable discharge that can be relied upon for water availability in the Kalukku watershed and the value of raw water availability in meeting water needs in irrigation areas in Kalukku. The aim of this research is to determine the amount of reliable discharge that can be relied upon for water availability in the Kalukku watershed and to determine the value of raw water availability in meeting water needs in irrigation areas in Kalukku. This research focuses on the irrigation area of the Kalukku River through the wide Kalukku Dam. The research results show that the mainstay discharge (Q80) of rainfall is 21.96 m3/sec, Q50 is 39.00 m3/sec, and Q20 is 60.06 m3/sec. The availability of irrigation water in D.I Kalukku is sufficient to meet the needs of rice plants in three growing seasons. There is a water surplus in MT1 and adequate supply in MT2 and MT3. This shows that D.I Kalukku has sufficient water supply for rice farming in that planting season. The availability of irrigation water is 128.9 m3/sec while the irrigation requirement is 17.7 m3/sec. This shows that there is enough water available to meet the needs of plants in MT3.